Study The Effect of Mindful Breathing Technique on Upper Back Pain Perception In Undergraduate Students - Rathod, Sagar; Tejani, Neelam; Rayjade, Amrutkuvar; Sharma, Seema; Patil, Swaroop (Journal of Neonatal Surgery, 2025)
Background Upper back pain is a common concern among undergraduate students, often arising from poor posture, prolonged sitting, and excessive use of electronic devices. Non-pharmacological interventions such as mindfulness-based techniques have proven to be effective in pain management and improving overall well-being. Objective This study aimed to investigate the effect of mindful breathing techniques on the perception of upper back pain in undergraduate students, evaluating changes in pain intensity both at rest and during movement. Results The results have shown a significant reduction in pain perception following the mindful breathing intervention. Statistical analysis revealed a significant p-values for reducing the pain intensity both at rest and during movement, indicating the effectiveness of mindful breathing techniques in alleviating upper back pain. In addition, participants reported improved emotional regulation and well-being. Conclusion Mindful breathing exercises have proved to be an effective, non-invasive, and cost-effective intervention for alleviating upper back pain among undergraduate students. Integrating mindfulness practices into academic settings may not only address physical discomfort but also promote emotional health and academic performance, contributing to a more holistic approach to student wellness